Development of Interactive Multimedia Using Macromedia Flash Equipped Drill Method about Human Digestive System Material for Students Grade XI - AL FENDRI; Lufri Lufri; Relsas Yogica (Bioeducation Journal, 2018)
The purpose of this research is to develop interactive multimedia using macromedia flash equipped with drill method about human digestive system material for high students senior high school class XI of valid and practical. This research uses Plomp development model that is initial investigation stage, development stage or prototype making and assessment phase. Research data were analyzed by qualitative and quantitative analysis. The data collection instrument uses self evaluation questionnaire, validity questionnaire, one to one evaluation questionnaire, small group evaluation questionnaire, field test questionnaire and questionnaire of practice. The developed product is validated by 2 lecturers of biology and 1 biology teacher of SMAN 1 Bukit Sundi Kabupaten Solok, while for practicality done by 21 students of SMAN 1 Bukit Sundi. Based on the research results obtained validity value 94.33 with criteria very valid, practicality by teacher 93,76 with criteria very practical and practicality of student 93,02 with criterion very practical.